Melatonin Application in Assisted Reproductive Technology: A Systematic Review and Meta-Analysis of Randomized Trials - Hu, Kai-Lun; Ye, Xiaohang; Wang, Siwen; Zhang, Dan (Frontiers in Endocrinology, 2020)
Objective: To study whether melatonin treatment can increase clinical pregnancy rate and live birth rate in assisted reproductive technology (ART) cycles. Methods: Literature searches were conducted to retrieve randomized trials that reported the effect of melatonin treatment on ART outcomes. Databases searched included PubMed, EMBASE, Cochrane Library, Web Of Science, and Google Scholar. Results: Ten studies matched the inclusion criteria. Clinical pregnancy was reported in all of the included studies and live birth was reported in three studies. Melatonin treatment significantly increased the clinical pregnancy rate (OR = 1.43 (1.11, 1.86), power = 0.98, 10 RCTs, low-quality evidence) but not the live birth rate (OR = 1.38 (0.78, 2.46), power = 0.34, 3 RCTs, low-quality evidence). Melatonin treatment increased the number of oocyte collected (SMD = 0.34 (0.01, 0.67), 7 RCTs, low-quality evidence), the number of maturated oocyte (SMD = 0.56 (0.27, 0.85), 7 RCTs, low-quality evidence), and the number of good quality embryo (DM = 0.36 (0.18, 0.55), 3 RCTs, low-quality evidence). Melatonin treatment significantly increased the biochemical pregnancy rate (OR = 1.65 (1.14, 2.38), 6 RCTs, low-quality evidence) and had no significant effect on the miscarriage rate (OR = 1.28 (0.65, 2.51), 5 RCTs, low-quality evidence). Conclusion: Melatonin treatment significantly increases the clinical pregnancy rate but not live birth rate in ART cycles. Melatonin treatment also increases the number of oocyte collected, maturated oocyte, and good quality embryo. No clear evidence suggested that melatonin treatment increased the adverse events in ART cycles. The actual findings may be compromised due to the wide heterogeneity of the included IVF patients, from PCOS to low ovarian reserve.